Mortality and associated factors among community-acquired pneumonia patients: A cross-sectional study in a provincial referral hospital in Indonesia - Rosdiana, Dani; Siregar, Fajri M.; Ediwi, Nabila C.; Putri, Rahmi T.; Nurrahma, Zuyyina ER.; Elisabet, Adinda; Sarassari, Rosantia; Safari, Dodi; Ilmiawati, Cimi; Elliyanti, Aisyah (Narra Sains Indonesia, 2025)
Community-acquired pneumonia (CAP) poses a significant impact on the healthcare system due to rehospitalization and mortality. About one-third of hospitalized CAP patients died within one year. In addition to advanced age, vulnerable groups with comorbidities such as cancer, diabetes, and cerebrovascular disease (CVD) are more likely to suffer from severe CAP. The aim of this study was to investigate the factors linked to mortality in adult hospitalized CAP patients. The study extracted the medical records of patients aged ≥18 years, admitted to a referral hospital in Riau Province, who were diagnosed with CAP between January and December 2023. Multiple logistic regression step-wise analysis was employed to determine the factors associated with mortality in CAP patients. The study involved 334 patients with a median age of 58 years. Based on the confusion, urea, respiratory rate, blood pressure, and age ≥65 years (CURB-65) score, 11.9% of patients had severe CAP (CURB-65 scores 3 and 4). Age was a significant predictor of severe CAP (p≤0.001). The most prevalent comorbidities were malignancy (33.2%), CVD (30.2%), and diabetes (28.4%). Mortality incidence during hospitalization reached 35.9%. Significant factors associated with mortality in hospitalized CAP patients included renal dysfunction/elevated serum urea levels (p=0.031), CURB-65 score (p=0.023), vasopressor use (p≤0.001), mechanical ventilator use (p≤0.01) and steroid use (p=0.029). However, CVD was associated with a decreased risk of mortality (p=0.019). Gram-negative bacteria predominated, accounting for 50.6% of all positive isolates. Several significant factors were associated with mortality in adult patients hospitalized with CAP at referral Hospital in Riau, including renal dysfunction, CURB-65 score, vasopressor use, mechanical ventilator use, and steroid use. This finding underscored the importance of early identification factors in CAP patients.